2015
DOI: 10.1111/bjd.13934
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of topical resin lacquer, amorolfine and oral terbinafine for treating toenail onychomycosis: a prospective, randomized, controlled, investigator-blinded, parallel-group clinical trial

Abstract: Topical 30% resin lacquer and topical 5% amorolfine lacquer provided similar efficacy for treating dermatophyte toenail onychomycosis. However, orally administered terbinafine was significantly more effective in terms of mycological cure and clinical outcome than either topical therapy at the 10-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 59 publications
(135 reference statements)
1
28
0
Order By: Relevance
“…Furthermore, a network meta‐analysis of onychomycosis treatments (Gupta, Daigle, & Foley, ) pointed out that newly developed topicals (like efinaconazole topical solution 10% and tavaborole topicalsolution 5%) have improved ORs of mycological cure, but these ORs were not significantly greater than those of preexisting topical treatments (like amorolfine and ciclopirox). While topical 30% resin lacquer also showed the similar efficacy as amorolfine for treating onychomycosis (Auvinen et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, a network meta‐analysis of onychomycosis treatments (Gupta, Daigle, & Foley, ) pointed out that newly developed topicals (like efinaconazole topical solution 10% and tavaborole topicalsolution 5%) have improved ORs of mycological cure, but these ORs were not significantly greater than those of preexisting topical treatments (like amorolfine and ciclopirox). While topical 30% resin lacquer also showed the similar efficacy as amorolfine for treating onychomycosis (Auvinen et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…It was found that this combination had synergistic or additive effects on most dermatophytes, and had no antagonistic effects, amorolfine applied on the nail plate goes into the nail keratin and then through the nail bed, whereas systemic antifungals reach the nail via the nail bed and matrix by diffusion from the dermal vessels and via the matrix by incorporation into the growing onychocytes (Finlay, ), the multiple drugs with different antifungal mechanisms should be used to treat refractory dermatomycoses, especially onychomycosis. In the current study, we adopt amorolfine as the representative of topical treatments, because abundant, reliable information was available on the feasibility, outcomes, and potential side effects of amorolfine in the treatment of onychomycosis (Auvinen et al, ). There are some other topical antifungals available in the market, but it is difficult to assess their efficacy in monotherapy due to the different criteria of recruiting patients for investigations, different study periods and post‐treatment assessment (Tabara et al, ), there is one article which put amorolfine and ciclopirox in separate combination in comparison, it turns out that ciclopirox in combination is more efficient than amorolfine in combination, but we still need more evidence to verify it.…”
Section: Discussionmentioning
confidence: 99%
“…It was explained in 1 sample by contamination from adjacent Microsporum canis‐ infected samples in the laboratory. Furthermore, the source of 4 samples was the toenails, and toenail samples are known to have a high false‐negative rate in conventional tests . Two of the 4 respective patients also had documentation of past treatment for onychomycosis.…”
Section: Resultsmentioning
confidence: 99%
“…A proof‐of‐concept study on the feasibility and clinical efficacy of 30% resin lacquer to treat toenail onychomycosis was published in 2013 . The randomized controlled trial of Auvinen et al . in this issue of the BJD compares the efficacy, safety and cost of 30% resin lacquer against current ‘best practice’ – topical 5% amorolfine and systemic terbinafine – on a randomized 1 : 1 : 1 allocation, comparing the three individual approaches.…”
mentioning
confidence: 99%
“…Therefore, the concentration of a topical preparation on the dorsal nail plate may be 1000 times higher than the concentration of active antifungal molecules that reach the nail bed and matrix . Many will agree with the authors that efforts should be turned to researching, developing and optimizing existing preparations to improve their bioavailability and efficacy . This is especially important as both oral terbinafine and itraconazole, when used to treat a nonlife‐threatening condition, may rarely result in potentially life‐threatening drug reactions and hepatotoxicity.…”
mentioning
confidence: 99%